The Impact of Using Induction Stoves on Household Energy Expenditure in Denpasar City - Ni Putu Ganish Sanjiwani; I Wayan Sukadana (Universitas Nusantara PGRI Kediri, 2023)
In achieving the Sustainable Development Goals, goal number 7, namely Clean and Affordable Energy, can be implemented through several efforts, one of which is the transformation of household energy from using LPG to an induction stove. Even though every household has the choice to choose an energy source to be used in its household activities, in making this choice, a household will find out which energy source is safer, cleaner and more economical to support its household activities. Household energy expenditure is an aspect that is no less important in this consideration. In addition to the use of induction stove, there are several other factors that affect household energy expenditure, including the number of household members, the number of electronic goods used, installed electrical power and the area of ​​the residential building. This research was conducted in Denpasar City with sample selection using propensity score matching with the nearest neighbor matching approach in 3 sub-districts/villages, namely Penatih Sub-District, Kesiman Petilan Village, and Tonja Sub-District.